2009
DOI: 10.1016/j.visres.2008.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive changes of inner retina function in response to sustained pattern stimulation

Abstract: We have characterized adaptive changes of inner retina function in response to sustained pattern stimulation in 32 normal subjects with an age range 23 to 77 years by measuring changes of the pattern electroretinogram (PERG) as a function of time. Contrast-reversal stimuli had square-wave profile in space and time, with peak spatial and temporal frequency and high contrast to maximize response amplitude. The PERG signal was sampled over 5 minutes with a resolution of 15 s. PERG signals were non-stationary, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 55 publications
0
33
0
Order By: Relevance
“…11 PERG adaptation provides specific physiological information on RGC function, 11,12 as it is selectively altered in diseases such as glaucoma 31 and optic neuritis. 21 To explore the response dynamic range and intrinsic variability over a wide range of conditions relevant to clinical application, we investigated the PERGx method in different groups of subjects including younger normal controls, older normal controls, open-angle glaucoma patients with modest visual field defects, and NAION patients with severe visual field defects.…”
Section: Discussionmentioning
confidence: 99%
“…11 PERG adaptation provides specific physiological information on RGC function, 11,12 as it is selectively altered in diseases such as glaucoma 31 and optic neuritis. 21 To explore the response dynamic range and intrinsic variability over a wide range of conditions relevant to clinical application, we investigated the PERGx method in different groups of subjects including younger normal controls, older normal controls, open-angle glaucoma patients with modest visual field defects, and NAION patients with severe visual field defects.…”
Section: Discussionmentioning
confidence: 99%
“…It shortened the PERG latency. Amplitude and phase represent two distinct aspects of neural activity 18-20. Response amplitude is related to the number and vitality of retinal neurons contributing to the recorded electrical signal.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-two subjects were suspected of having glaucoma (GS, n=42, mean age 54.9±10.7 years); twenty-two had early manifest glaucoma (EMG, n=22, mean age 60.3 ±10.2 years), and sixteen were normal controls (NC, n=16; mean age 52.7 ±12.8 years) from a previous study. 7 No control subject had family history of glaucoma, suspicious glaucomatous optic disk, or IOP> 16 mm Hg. The mean ages of the groups were not significantly different (ANOVA, P=0.082).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been shown that the steady-state pattern electroretinogram (PERG) recorded during continuous presentation of fast-reversing, high-contrast, fine gratings displays slow adaptive changes of the response amplitude that have been interpreted as metabolic adaptation. 6, 7 In contrast, the flicker ERG — a measure of outer retina function — remains unchanged during continuous presentation of a luminance-modulated uniform field. 8 Altogether, these results imply that fast contrast-reversing patterns induce adaptive functional changes in the inner, but not outer, retina in response to changed metabolic requirements.…”
Section: Introductionmentioning
confidence: 99%